Corruption as Business Challenge in Pakistan - Yahya Khan; Gabor Rethi; Krisztina Szegedi (European Scientific Journal, ESJ, 2018)
Corruption is a curse for any country, as it negatively affects the economic activities and drags the whole society to worst conditions by increasing the poverty and social inequities. Recently the most critical factor for doing business in Pakistan is corruption. In order to give a comprehensive picture of corruption in Pakistan this article (1) critically analyses the literature regarding corruption, its impact on society and the business environment specifically in Pakistan, (2) focuses on business-related factors of corruption, (3) presents various anti-corruption initiatives of Pakistani companies and foreign good examples. Based on our research this study emphasizes that the government should take corrective actions and strengthen institutions and should work in collaboration with the private and civil sector to control the uprising corruption problems. Awareness against corruption in business sphere and general public is very much needed and implementing possible anti-corruption tools, companies can positively contribute to the fight against corruption and Pakistan's economic and social development.